Natural variation of OsLG3 controls drought stress tolerance in rice by inducing ros scavenging - Xiong, Haiyan; Yu, Jianping; Li, Jinjie; Wang, Xin; Liu, Pengli; Zhang, Hongliang; Zhao, Yan; Yin, Zhigang; Li, Yang; Guo, Yan; Fu, Binying; Wang, Wensheng; et al. (Cold Spring Harbor Laboratory, 2017)
Improving performance of rice under drought stress has potential to significant impact on rice productivity. Previously we reported that OsLG3 positively control rice grain length and yield.ResultsIn this study, we found that OsLG3 was more strongly expressed in upland rice compared to lowland rice under drought stress condition. Candidate gene association analysis showed that the natural variation in OsLG3 was associated with tolerance to water deficit stress in germinating rice seeds. Transgenic rice with enhanced OsLG3 expression exhibited improved tolerance to drought and that is most likely due to enhanced ROS scavenging efficiency. Phylogenetic analysis and pedigree records indicated that the tolerant allele of OsLG3 has potential to improve drought tolerance of japonica rice.ConclusionsCollectively, our work revealed that the natural variation of OsLG3 contributes to rice drought tolerance and the elite allele of OsLG3 is a promising genetic resource for the development of drought-tolerant and high-yield rice varieties.